Five Minutes a Day Makes Tone Quality Stay - Iovine, Laura (Valdosta State University, 2005)
The purpose of this study was to describe effective strategies for improving high school instrumental students' tonal qualities by using small group learning coupled with computer communication technology. The instructional unit was taught over the course of 4 weeks as part of regular instruction in a high school band class. Thirty-five participants completed all activities. This qualitative study included observation, interview, focus group, pre- and postintervention assessment, pre- and post-intervention survey, Minute Papers, and Weekly Accountability Reports. Each participant worked as a member of a small group that focused on unique approaches to performing long tones on musical instruments. Students communicated their efforts and results both individually and as part of their groups through email, PowerPoint, and Minute Papers. Findings suggest that students increased their ability to hold a long tone and that working in small groups improved student learning. Participants indicated that holding a note as long as possible improved their tone quality, intonation, and expressive capabilities. The results of the study were communicated to the learning community through a PowerPoint presentation emailed to all system music teachers. The presentation emphasized the positive results obtained for one band and contained all necessary items for area teachers to duplicate this instructional strategy should they desire.
Keywords: Instrumental students; Group learning; Computer communication technology; Educational technology; Teaching--Aids and devices; Computer-assisted instruction